Impact of foliar application of aminoethoxyvinylglycine on pre-harvest fruit drop and quality in mandarin cv. kinnow (Citrus reticulata L. Blanco) - Iftikhar, Asad; Hussain, Zahoor; Khadija, Faheem; Sarwar, Ghulam; Khan, Muhammad Nawaz; Salik, Muhammad Raza; Ahmad, Imtiaz (Journal of Pure and Applied Agriculture, 2023)
Citrus fruit drop is a serious issue in citrus producing countries of the world as well as in Pakistan. The pre-harvest foliar application of aminoethoxyvinylglycine (AVG) @ 150, 300 and 600 mg L -1 were applied at mature and color break stage to evaluate its influence on fruit drop and quality of kinnow. Exogenous application of AVG (300 and 600 mg L-1 ) at both mature and color break stage significantly reduce fruit drop in kinnow as well as improve the fruit quality. However, exogenous application of AVG with 300 mg L-1 at color break stage was the most effective in reducing fruit